INNOVATION IN SOCIAL MEDIA STRATEGY: A STUDY OF SMEs IN JEMBER - Maftah, Milatul; Zulianto, Mukhamad (Jurnal Bisnis dan Manajemen (JBM), 2023)
Promotion is the key to spreading information about a business or product. Today, SMEs utilize social media for promotion. Because social media has a wider range, promotion is done by seizing social media to reach a wider market share. This research aims to analyze the utilization of social media as a promotional medium by SMEs in the Jember Regency. The research results show that SMEs utilize social media for promotion, such as Facebook, Whatsapp, Instagram, and Telegram. Each social media is used following the functions and features. Social media Instagram is utilized as a place to upload promotional videos, product photos, posters, booking info, and product reviews. Social Media Facebook is utilized to reach people who are in the community to sell and buy. Social Media WhatsApp and Telegram can be used for two-way communication between SMEs and consumers. Keywords: social media, Strategy, Small and medium-sized Enterprises